Experimental and 3D numerical analysis on the effect of specimen thickness on fracture toughness of Al6061-SiC-cenosphere Hybrid composites (Fracture and Structural Integrity, 2025)
This study examines the fracture toughness of Al6061 alloy-based hybrid composites reinforced with silicon carbide particles and cenosphere microspheres. Aluminum alloy Al6061 is widely utilized in structural applications due to its balanced mechanical properties, and its hybridization with SiC and cenosphere reinforcements enhances its performance under critical loading conditions. The effect of specimen thickness on fracture toughness was examined by fabricating compact tension specimens in accordance with ASTM E399 standards, with thickness-to-width ratios ranging from 0.2 to 0.7. Controlled fatigue cracks were introduced, and both experimental testing and finite element simulations were conducted to assess the critical stress intensity factor and crack propagation behaviour across different thicknesses. Results show that the fracture toughness is constant after the B/W ratio of 0.5 and above, states as plane strain fracture toughness. The 3wt% SiC and 6wt% cenosphere in Al6061 shows the highest fracture toughness up to 15.56 MPa√m, due to the effective stress distribution and interfacial bonding. The fractography using the scanning electron microscopy reveals that particle debonding is major failure mechanism, with microcracking in 3wt% cenosphere composites and crack deflection and stress transfer at high reinforcement contents. Experimental results were well matched with the simulation model with ±10% differences, proving its validity.
Keywords: Al6061 alloy; a/W, B/W ratios; Fracture toughness; CT specimens; Cenosphere